2003
DOI: 10.1046/j.1365-2621.2003.00688.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ethanol concentration on the efficiency of extraction of ginseng saponins when using a microwave‐assisted process (MAP™)

Abstract: This research determined the effect of ethanol concentration (vol.%) on the extraction of saponins from ginseng using a microwave-assisted process (MAP TM ) at different powers under atmospheric pressure conditions. The optimized particle size of ginseng roots and mass-to-solvent volume ratio were 60 mesh and 1 : 10 (g mL )1 ), respectively. The yields of total solids and crude saponins were influenced by ethanol concentration, with the highest value at 45-60% for the former and 60-75% for the latter, at micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(23 citation statements)
references
References 8 publications
2
21
0
Order By: Relevance
“…Similarly, recovery of quinoa saponins obtained using aqueous ethanol and methanol was higher than that of water and pure alcohol solvents (Muir et al, 2002). Maximum ginsenoside yield from ginseng was obtained by 60-75% ethanol in the range of 30-90% ethanol (Kwon, Lee, Bélanger, & Paré, 2003), while the highest saponin recovery from Glinus lotoides seeds was achieved using 60% methanol (in 0-100% methanol range) (Endale, Schmidt, & Gebre-Mariam, 2004).…”
Section: Saponin Yieldmentioning
confidence: 99%
“…Similarly, recovery of quinoa saponins obtained using aqueous ethanol and methanol was higher than that of water and pure alcohol solvents (Muir et al, 2002). Maximum ginsenoside yield from ginseng was obtained by 60-75% ethanol in the range of 30-90% ethanol (Kwon, Lee, Bélanger, & Paré, 2003), while the highest saponin recovery from Glinus lotoides seeds was achieved using 60% methanol (in 0-100% methanol range) (Endale, Schmidt, & Gebre-Mariam, 2004).…”
Section: Saponin Yieldmentioning
confidence: 99%
“…It was reported that MAE was used for the extraction of pollutants from environmental samples (Camel, 2000), saponins from ginseng (Kwon, Bélanger, Paré, & Yaylayan, 2003b;Vongsangnak, Gua, Chauvatcharin, & Zhong, 2004), glycyrrhizic acid from licorice root (Pan, Liu, Jia, & Shu, 2000). Moreover, optimization of microwave-assisted extraction for ginseng components by response surface methodology was reported by Kwon et al (Kwon, Bélanger, & Paré, 2003a;Kwon, Lee, Bélanger, & Paré, 2003c;Kwon, Lee, Kim, Bélanger, & Paré, 2004). The effects of ethanol concentration, microwave power and processing time on extraction of total solids, crude saponin and individual ginsenosides were determined in these studies.…”
Section: Introductionmentioning
confidence: 99%
“…It has also been used for the selection of the appropriate ethanol content in the extraction medium, the extraction temperature and the extraction time when maximising antioxidant activity of defatted borage meal (Wettasinghe & Shahidi, 1999). In previous studies by Ganthavorn & Hughes (1997) it was shown that the particle size of the sample, 25 mesh, was sufficient to extract polyphenolic compounds from dry beans ( Phaseolus vulgaris ) and Kwon et al. (2003a,b) showed that an extraction solvent ratio of ethanol to sample 1:10 was suitable for the extraction of saponin components of ginseng when using a microwave‐assisted process (MAP TM ).…”
Section: Introductionmentioning
confidence: 99%